Assessment of in vitro gas and methane production of diet fortified with yeast and lactobacilli spp (2016)
The effect of dietary fortification of two levels of bakers yeast and yeast plus Lactobacilli against negative control and positive control (antibiotic) was assessed on in vitro gas production (IVGP) kinetics and methane production at 24 hours incubation. A concentrate diet was formulated and fortified with six levels consisting: control (D1); antibiotic (D2); 2.5 g bakers yeast (D3); 5.0 g bakers yeast (D4); 2.5 g yeast plus Lactobacilli (D5) and 5.0 g yeast plus Lactobacilli (D6) and mixed with Panicum maximum to serve as the substrate in a completely randomized design. The parameters tested were IVGP, organic matter digestibility (OMD), metabolizable energy (ME), short chain fatty acids (SCFA), methane gas, degradability, partitioning factor and microbial biomass. Higher (P0.05) IVGP volumes, in vitro organic matter degradability, metabolizable energy (ME) and short chain fatty acid (SCFA) were recorded for diets D3 to D6 and D1 over D2, whereas the difference amongst D3 to D6 and D1 was not significant (P>0.05). Highest IVGP was recorded for D6 (16.33 ml) and the lowest (4.33 ml) in D2. Gas production from the soluble fraction (a), rate of constant of gas production (c) and time (t) were not significantly different (p > 0.05) while the gas production from the insoluble fraction (b), potential extent of gas production (a + b) differed significantly (p < 0.05). For methane gas, D3 recorded the highest (5.00 ml / 200 mg DM) and D2 had the lowest (1.67 ml / 200 mg DM). All other fortifications were higher in methane gas than control. The present study demonstrated the potential of probiotics especially when mixed at 5 g level in improving degradation.